Growth Hormone-Releasing Hormone in Diabetes - Fridlyand, Leonid E.; Tamarina, Natalia A.; Schally, Andrew V.; Philipson, Louis H. (Frontiers in Endocrinology, 2016)
Growth hormone-releasing hormone (GHRH) is produced by the hypothalamus and stimulates growth hormone synthesis and release in the anterior pituitary gland. In addition GHRH is an important regulator of cellular functions in many cells and organs. Expression of GHRH G-Protein Coupled Receptor (GHRHR) has been demonstrated in different peripheral tissues and cell types including pancreatic islets. Among the peripheral activities, recent studies demonstrate a novel ability of GHRH analogs to increase and preserve insulin secretion by beta-cells in isolated pancreatic islets, which makes them potentially useful for diabetes treatment. This review considers the role of GHRHR in the beta-cell and addresses the unique engineered GHRH agonists and antagonists for treatment of Type 2 diabetes mellitus. We discuss the similarity of signaling pathways activated by GHRHR in pituitary somatotrophs and in pancreatic beta-cells and possible ways as to how the GHRHR pathway can interact with glucose and other secretagogues to stimulate insulin secretion. We also consider the hypothesis that novel GHRHR agonists can improve glucose metabolism in Type 2 diabetes by preserving the function and survival of pancreatic beta-cells. Wound healing and cardioprotective action with new GHRH agonists suggesting that they may prove useful in ameliorating certain diabetic complications. These findings highlight the future potential therapeutic effectiveness of modulators of GHRHR activity for the development of new therapeutic approaches in diabetes and its complications.